Occupational, dietary, and other risk factors for myelodysplastic syndromes in Western Greece. Issue 7 (9th August 2017) - Avgerinou, Christina; Giannezi, Ioanna; Theodoropoulou, Stela; Lazaris, Vasileios; Kolliopoulou, Georgia; Zikos, Panagiotis; Alamanos, Yannis; Leotsinidis, Michalis; Symeonidis, Argiris
ABSTRACT: Purpose: We have observed an increasing incidence of myelodysplastic syndromes (MDS) in the geographic area of Western Greece during the past two decades. The objective of this study was to investigate potential risk factors for the manifestation of MDS in this area of Greece. Methods: A hospital-based case–control study was conducted in the public hospitals of the region. Participants were interviewed based on a questionnaire regarding demographics, occupational exposures, smoking, alcohol consumption, dietary, and domestic factors. Results: A total of 228 individuals (126 cases, 102 controls) were recruited in this study. Univariate analysis showed that risk of MDS was associated with a family history of hematologic malignancy or solid tumor, exposure to pesticides, insecticides, herbicides, increased weekly intake of meat and eggs, and increased alcohol intake, whereas fruit intake had a protective effect. Analysis by pesticide ingredient showed a weak association of exposure to paraquat and glyphosate with the occurrence of MDS. Multivariate analysis showed that independent risk factors for the manifestation of MDS were family history of solid tumor (OR 2.47, 95% CI 1.32–4.65), meat intake for ≥5 days/week (OR 2.67, 95% CI 1.05–6.80) and exposure to pesticides (OR 3.25, 95% CI 1.73–6.11). Conclusions: Exposure to pesticides is a major risk factor of MDS in Western Greece. Family history of solid tumor and increased meat intake also appear to play a role in the pathogenesis of MDS. Public health authorities should implement policies to advise and protect farmers from the harmful effects of agrochemicals. Emphasis should also be given to health promotion advice including healthy eating.